Determination of effective source to surface distance for electron beam from siemens primus linear accelerator - Ping, Heng Siew (2004)
The aim of this thesis is to determine the effective source surface distance for 6, 9 and 15 MeV electron beam energies generated from Siemens Primus linear accelerator in HUSM. The effective SSD is the distance from the virtual source position to the end of the applicator. The effective SSD is known to depend on beam energy and field size. Different methods of obtaining the effective source surface distance for electron beams have been investigated. The charge measurements were performed using parallel plate ionization chamber in solid water phantom at depth of dmax, using 0, 5, 10 and 15cm air gap. Excel was used to present a plot of [QJQ8 ] 112 versus air gap. The variation of the effective SSD with the energy and field size of measurement was also investigated. Minimum effective SSD was 58.3 em in small field size of 5 em diameter circle applicator and maximum effective SSD was 98.2 em for 25x25 cm2 applicator, with 6 MeV energy. Effective SSDs gradually increased with field size for the same electron energy and decreased again at 25x25cm2 for 6 and 9MeV. Effective SSDs gradually increased with the electron energies. From the results we recommended that the effective SSD should be measured for each energy and field size before clinical use.